Future vision of the Peruvian coal - Luyo Quiroz, Antonio (2011)
In our country for decades one has mentioned our coal, even forts have been invested sums of money trying to study this resource, his access, exploitation and industrialization. Entities like INGEMMET, Mining Peru and Sider Perú, they have invested in projects as The mining industry of the Coal, Transport of solid for pipelines, exploitation of the coal of Oyón and Evaluation for the extraction of the Coal of Holy. It has been a question of investigating on his utilization and the way of taking it towards the centers of consumption, has planned to become Thermoelectric in the zones of production to avoid his movement, direccionando has been a question to design and transform the existing machines this to the production of the Coal due to the fact that on the domestic market only machines exist for the mining metallic production, but what results have been had?, in this article we want to answer questioning this one and to think about the future of this resource. In the works of investigation there interfered two state institutions INGEMMET and Miner Peru and particular Sider Perú, one counted as base in the studies the works realized by the Engineer Hugo Escudero Rato, who I study The Coal of Peru, he studied deeply the Coal of Holy and coordinated the works done by the German Fund KFW at the expense of the division of INGEMMET's Mining industry, obtaining some results that we will explain in the following article.